Validitas Reliabilitas Kuesioner BCTQ Indonesia pada Dokter Gigi CTS: Studi Cross-Sectional Samarinda - Wahyuni Dwi Cahya; Sulfandi Sulfandi; Rezky Amaliah Usman; Ashifa Quamila (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Boston Carpal Tunnel Questionnaire (BCTQ) is a leading instrument for assessing symptom severity and functional status in Carpal Tunnel Syndrome (CTS), yet evidence of its validity among dentists in Indonesia remains limited. This cross-sectional study involved 55 dentists with confirmed CTS (positive Phalen and Tinel tests) in Samarinda who self-administered the Indonesian version of the BCTQ (11-item Symptom Severity Scale and 8-item Functional Status Scale). Construct validity was tested using Pearson correlation and internal reliability using Cronbach’s alpha. Subjects comprised 44 females (80.0%) and 11 males (20.0%) with a mean age of 44.7 years. All 11 Symptom Severity Scale items had correlation coefficients of 0.486–0.789 (p<0.01) and the 8 Functional Status Scale items 0.492–0.827 (p<0.01), all exceeding the critical r table value (0.266). Cronbach’s alpha was 0.884 for the Symptom Severity Scale and 0.870 for the Functional Status Scale, both classified as excellent. Therefore, the Indonesian version of the BCTQ is valid and reliable for use among dentists with CTS and is recommended as a screening and treatment outcome evaluation tool in this high-risk population.